PERAN TAX TREATY SEBAGAI INSTRUMEN HUKUM UNTUK MENINGKATKAN INVESTASI ASING DI INDONESIA: The Role Of Tax Treaties As Legal Instruments In Promoting Foreign Investment In Indonesia - Noor, Akbarudin (Ganec Swara, 2026)
The Double Taxation Agreement, commonly referred to as a Tax Treaty, serves as an international legal instrument designed to prevent investors from being taxed twice on the same income. This study explores the role of Tax Treaties in strengthening Indonesia’s investment climate by providing legal certainty and reducing fiscal risks for foreign investors. Using a normative juridical approach, the research examines national regulations, international agreements, and practical implementation in Indonesia. The findings suggest that Tax Treaties not only ease the tax burden for cross-border investors but also enhance trust in Indonesia’s legal and fiscal framework, thereby increasing the country’s competitiveness as an investment destination. Nevertheless, the effectiveness of Tax Treaties depends on consistent law enforcement, the administrative capacity of tax authorities, and the government’s ability to balance national fiscal interests with international commitments. In conclusion, optimizing Tax Treaties as a legal instrument requires synergy between fiscal policy, regulatory reform, and international diplomacy to ensure sustainable growth of foreign investment in Indonesia.